2012
DOI: 10.1186/1471-2229-12-151
|View full text |Cite
|
Sign up to set email alerts
|

A naturally occurring InDel variation in BraA.FLC.b (BrFLC2) associated with flowering time variation in Brassica rapa

Abstract: BackgroundFlowering time is an important trait in Brassica rapa crops. FLOWERING LOCUS C (FLC) is a MADS-box transcription factor that acts as a potent repressor of flowering. Expression of FLC is silenced when plants are exposed to low temperature, which activates flowering. There are four copies of FLC in B. rapa. Analyses of different segregating populations have suggested that BraA.FLC.a (BrFLC1) and BraA.FLC.b (BrFLC2) play major roles in controlling flowering time in B. rapa.ResultsWe analyzed the BrFLC2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 29 publications
(42 reference statements)
0
57
1
2
Order By: Relevance
“…The PC-175 sequence did not have this deletion and was identical to the reference Chinese cabbage sequence in this region. Wu et al (2012) sequenced BrFLC2 alleles from Yellow sarson (accession L143), three Chinese cabbage genotypes, Rapid cycling (accession L144), Mizuna, Neep greens, Turnip, and Caixin, and identified a discontinuous 57bp insertion/deletion (InDel) across exon 4 and intron 4 in Yellow sarson resulting in a non-functional allele (Wu et al , 2012). This deletion was absent in all other vegetable accessions they tested and present in many of the tested oil types, and homozygous in the three Yellow sarson accessions tested, but absent in the other accessions they tested.…”
Section: Discussionmentioning
confidence: 99%
“…The PC-175 sequence did not have this deletion and was identical to the reference Chinese cabbage sequence in this region. Wu et al (2012) sequenced BrFLC2 alleles from Yellow sarson (accession L143), three Chinese cabbage genotypes, Rapid cycling (accession L144), Mizuna, Neep greens, Turnip, and Caixin, and identified a discontinuous 57bp insertion/deletion (InDel) across exon 4 and intron 4 in Yellow sarson resulting in a non-functional allele (Wu et al , 2012). This deletion was absent in all other vegetable accessions they tested and present in many of the tested oil types, and homozygous in the three Yellow sarson accessions tested, but absent in the other accessions they tested.…”
Section: Discussionmentioning
confidence: 99%
“…In B. oleracea , only BolFLC2 contributes to the control of flowering time . In B. rapa , BraFLC1 and BraFLC2 are candidate genes for the flowering time and vernalization response QTL in B. rapa …”
Section: Discussionmentioning
confidence: 99%
“…In B. rapa , BraFLC1 and BraFLC2 are candidate genes for the flowering time and vernalization response QTL in B. rapa . Deletion mutation across exon 4 and intron 4 in BrFLC2 gene contributes greatly to variation in flowering time in oil‐type B. rapa …”
Section: Introductionmentioning
confidence: 99%
“…Schranz et al (2002) and Franks et al (2015) reported presence of four FLC paralogues in B. rapa (BrFLC1,BrFLC2,BrFLC3,and BrFLC5). A genetic-genomics approach revealed that BrFLC2 is a major regulator of flowering time in B. rapa (Wu et al 2012;Xiao et al 2013;2014). Recently, Li et al (2016) reported that early flowering phenotypes of B. rapa is related to be nonfunctional BrFLCs which are truncated form by premature termination, but slow or late flowering types contain functional or intact forms of BrFLC1, BrFLC2, and BrFLC3.…”
Section: Expression Of Flowering-related Genesmentioning
confidence: 99%